2014
DOI: 10.1007/s00384-014-1850-x
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 gene mutations in ulcerative colitis: useless or misunderstood?

Abstract: Purpose NOD2 mutations have been linked to an increased risk of Crohn's disease and to some of its phenotypes. The association between NOD2 mutations and susceptibility to ulcerative colitis (UC) remains somewhat controversial and potential correlations between these mutations and UC phenotype have not been studied. Aim To assess whether NOD2 mutations are a risk factor for UC in Portugal and if there are any genotype-phenotype correlations in these patients. Methods The three main NOD2 mutations were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…These autoimmune diseases responsible genes might be critical for the development of CD. Recently, study found that CXCL5 [454], S100A12 [455], OSM (oncostatin M) [456], LRG1 [457], LCN2 [458], CXCL1 [459], S100A9 [460], IFITM1 [461], XBP1 [462], MMP3 [457], IFITM3 [463], IL1B [464], GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478], CFB (complement factor B) [479], CD14 [480], GPR84 [481], PCSK9 [482], FOXP3 [483], LPL (lipoprotein lipase) [484], IL1R2 [485], TLR2 [486], MEFV (MEFV innate immuity regulator, pyrin) [487], VWF (von Willebrand factor) [488], NOD2 [489], DMBT1 [490], HSPA6 [491], TIMP1 [492], ICAM1 [493], EGR1 [494], CCL11 [495], IFNG (interferon gamma) [496], APOE (apolipoprotein E) [497] FGR (FGR proto-oncogene, Src family tyrosine kinase) [498], IL6 [499], SPP1 [192], IL11 [500], RNF186 [501], MMP2 [502], CD24 [503], SPHK1 [504], GZMB (granzyme B) [505], MUC5AC [506], SERPINA3 [507], TWIST1 [508], PLAU (plasminogen activator, urokinase) [509], CA2 [510], CA9 [510], CTLA4 [511], PADI4 [512], MMP13 [513], MPO (myeloperoxidase) [244], LEFTY1 [514], CA1 [515], MMP7 [513], ABCG2 [516], CYP2J2 [517], AICDA (activation induced cytidine deaminase) [518], CYP2D6 [519], CYP3A5 [52...…”
Section: Discussionmentioning
confidence: 99%
“…These autoimmune diseases responsible genes might be critical for the development of CD. Recently, study found that CXCL5 [454], S100A12 [455], OSM (oncostatin M) [456], LRG1 [457], LCN2 [458], CXCL1 [459], S100A9 [460], IFITM1 [461], XBP1 [462], MMP3 [457], IFITM3 [463], IL1B [464], GBP5 [465], HGF (hepatocyte growth factor) [466], CXCL9 [467], SLC11A1 [468], IL1RN [469], STAT1 [470], CYP27B1 [471], MMP1 [472], SOCS3 [473], TLR8 [474], CD55 [475], CCL28 [476], FCGR2A [477], CCL2 [478], CFB (complement factor B) [479], CD14 [480], GPR84 [481], PCSK9 [482], FOXP3 [483], LPL (lipoprotein lipase) [484], IL1R2 [485], TLR2 [486], MEFV (MEFV innate immuity regulator, pyrin) [487], VWF (von Willebrand factor) [488], NOD2 [489], DMBT1 [490], HSPA6 [491], TIMP1 [492], ICAM1 [493], EGR1 [494], CCL11 [495], IFNG (interferon gamma) [496], APOE (apolipoprotein E) [497] FGR (FGR proto-oncogene, Src family tyrosine kinase) [498], IL6 [499], SPP1 [192], IL11 [500], RNF186 [501], MMP2 [502], CD24 [503], SPHK1 [504], GZMB (granzyme B) [505], MUC5AC [506], SERPINA3 [507], TWIST1 [508], PLAU (plasminogen activator, urokinase) [509], CA2 [510], CA9 [510], CTLA4 [511], PADI4 [512], MMP13 [513], MPO (myeloperoxidase) [244], LEFTY1 [514], CA1 [515], MMP7 [513], ABCG2 [516], CYP2J2 [517], AICDA (activation induced cytidine deaminase) [518], CYP2D6 [519], CYP3A5 [52...…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, association studies among Indian IBD patients have shown a weak relationship of the NOD2 gene mutations with UC, but not with CD [31]. In turn, the study of NOD2 gene variants in patients with UC in the Portuguese population did not correlate them with increased risk of the disease; however, a tendency for a more aggressive course of the disease was observed among carriers of rare NOD2 variants [32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that UC and Crohn’s disease are related pathologies, there are differences in some of the susceptibility alleles. For example, if Nod2 was one of the first genes to be associated with Crohn’s disease, only later on a studied developed by Freire et al [ 30 ] correlated the Nod2 mutations with a more aggravated condition for UC patients. Moreover, patients with Nod2 mutations have been associated with defective Atg16L1 recruitment, leading to autophagy induction [ 31 ].…”
Section: Inflammasomesmentioning
confidence: 99%